Intelligence from the Open Web: OSINT and Forensic Investigation of Social Media - Amrica Mule (AG Volumes, 2026)
Open Source Intelligence (OSINT) is a vital component in digital forensic investigations today as it allows investigators to gather and analyze information that is available in the public domain. Social media platforms have grown significantly, leaving behind huge digital traces that can be useful in cybercrime investigations, fraud detection, missing person investigations, terrorism monitoring and intelligence gathering. This review will discuss the basics of OSINT and Social Media Intelligence (SOCMINT), the major OSINT techniques used in forensic investigations, and how these techniques are used in the social media world. The paper also identifies some of the significant issues, such as protection of privacy, legal jurisdiction, authenticity of data and cross-platform investigations, especially the Indian perspective. Additionally, the authors explore new technologies that have the potential to enhance the efficiency, accuracy, and reliability of future OSINT-based forensic investigations, including artificial intelligence, machine learning, natural language processing and predictive analytics.